Comparison of Sphenopalatine Block and Intravenous Paracetamol for the Treatment of Post-Dural Puncture Headache - Khan, Abid; Feroz, Shizan Hamid; Iqbal, Sana; Sultan, Muhsan; Munir, Sajid; Ahmed, Waqas (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effect of topical sphenopalatine block and intra venous Paracetamol in the management of post-Dural puncture headache.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital Peshawar Pakistan, from Jan to Aug 2021.Methodology: This experimental study was conducted on 153 patients who underwent lumbar puncture for any procedure and then suffered from post-Dural puncture headaches. Patients were randomized into two groups. Group A received the topical sphenopalatine block, while group B received the intravenous Paracetamol three doses 12 hours apart. Headache was recorded on Numeric pain score (NPS) 24 hours after the surgical procedure. Comparison in pain relief was compared in both groups at 1 hour, 12 hours, 24 hours and 48 hours.Results: Out of 153 patients randomized into two groups, 76 (49.7%) were categorized into Group-A, and 77 (50.3%) were categorized into Group-B. 63 (41.2%) were male, while 90 (58.8%) were female. The mean age of patients included in our study was 34.34 ± 4.33 years. Gynaecological/obstetric procedures 70 (45.7%) were the most common indication for lumbar puncture in our study. At 1, 12, 24 and 48 hours, pain relief was statistically significantly better in Group-A than in Group-B (p- value